Reactions of gold(I) electrophiles with nucleophiles derived from group 6 Fischer-type carbene complexes - Esterhuysen, Matthias Wilhelm (Stellenbosch : University of Stellenbosch, 2011)
Dissertation (PhD)--University of Stellenbosch, 2003.